PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KEPERCAYAAN TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS NASABAH KREDIT PT PEGADAIAN (PERSERO) CABANG DEMAK - Ria Ega Mu’arotun; Euis Soliha (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze the effect on customer relationship management and trust on satisfaction and its impact on customer loyalty. This research was conducted on credit customers of PT. Pegadaian (Persero) Demak Branch. The sample in this study used a sampling technique, namely purposive sampling by taking 100 respondents. The results of this study indicate that there is a positive and significant influence between the customer relationship management variables on customer satisfaction. The trust variable has a positive and significant effect on customer satisfaction. The customer relationship management variable has a positive but not significant effect on customer loyalty. The trust variable has a positive and significant effect on customer loyalty. The satisfaction variable has a positive and significant effect on customer loyalty. Keywords : Customer Relationship Management, Trust, Satisfaction, Loyalty